Advances of optical miniscopes for in vivo imaging of neural activity in freely moving animals - Chen, Kunpeng; Tian, Zhaoshi; Kong, Lingjie (Frontiers in Neuroscience, 2022)
To study neural mechanisms of ethologically relevant behaviors including many social behaviors and navigations, optical miniscopes, which can be carried by the model animals, are indispensable. Recently, a variety of optical miniscopes have been developed to meet this urgent requirement, and successfully applied in the study of neural network activity in free-moving mice, rats, and bats, etc. Generally, miniature fluorescence microscopes can be classified into single-photon and multi-photon fluorescence miniscopes, considering their differences in imaging mechanisms and hardware setups. In this review, we introduce their fundamental principles and system structures, summarize technical advances, and discuss limitations and future trends, for in vivo imaging of neural activity in freely moving animals.